EDUCAÇÃO FINANCEIRA COM IDOSOS: UM RELATO DE EXPERIÊNCIA DESENVOLVIDO PELO NÚCLEO DE APOIO AO SUPERENDIVIDADO DE CANOAS - Pereira de Souza, Cristina (2023)
In front of the significant increase in the elderly population, interventions with this audience are important tools for guaranteeing and maintaining rights. Studies indicate that elderly people in more socially and economically vulnerable situations may be more susceptible to economic violence, leading, for example, to conditions such as over-indebtedness. Over-indebtedness is a multifactorial social phenomenon with serious repercussions on the quality of life, well-being, and health of individuals. In this scenario, the team from the Support Center for Over-indebted Individuals (NAS), linked to the PROCON of the municipality of Canoas/RS, carried out pedagogical and preventive interventions aimed at building knowledge about financial education, changing financial and consumption habits. Through the methodology of experience reports, we narrate the experiences of 11 interventions with groups of elderly people with an average age of 65 years, covering a total of 226 participants. From the development of this work, it was possible to reflect on the importance and impact of teaching financial education to the elderly. As many participants recognized themselves as victims of financial frauds and scams, which highlights the need to strengthen public policies aimed at this topic, as well as more studies that can expose this reality in other contexts.